Solvent‐Assisted Anisotropic Cleavage of Transition Metal Carbide into 2D Nanoflakes. Issue 11 (12th November 2021) - Hu, Chen-Xia; Tian, Zhen; Xiao, Qi; Zhu, Zhen-Tong; Li, Xiang-Yang; Dun, Guan-Hua; Wu, Hao-Ran; Tang, Yu-Long; Wang, Qiang; Zhang, Hao-Li
Abstract : 2D Transition Metal Carbides Nanoflakes In article number 2100039, Yu‐Long Tang, Qiang Wang, Hao‐Li Zhang, and co‐workers fabricate 2D nanoflakes from nonlayered transition metal carbides by a solvent‐assisted anisotropic cleavage method utilizing the intrinsic anisotropic hardness properties. The nonlayered 2D nanoflakes are successfully applied in ultrafast photonic as saturable absorbers. This method paves a new way for the fabrication of novel 2D nanomaterials.